Rate of Comorbidities in Giant Cell Arteritis: A Population-based Study - Aladdin J Mohammad; Martin Englund; Carl Turesson; Gunnar Tómasson; Peter A. Merkel (2016)
To compare the rate of occurrence of comorbidities, including severe infections, in a population-based cohort of patients with biopsy-proven giant cell arteritis (GCA) with a reference population in Southern Sweden.The study included a population-based cohort of biopsy-proven GCA cases diagnosed between 1998 and 2010 from the Skåne region in Southern Sweden (population: 1.2 million). For each patient, 4 reference subjects were identified from the general population and matched for age, sex, area of residence, and date of diagnosis of GCA. Using the Skåne Healthcare Register, comorbidities and severe infections (requiring hospitalization) diagnosed after GCA onset were identified. The rate of the first occurrence of each comorbidity was the result of dividing the number of subjects with a given comorbidity by the person-years of followup. The rate ratio (RR; GCA:reference population) was also calculated.There were 768 patients (571 women) with GCA and 3066 reference persons included in the study. The RR were significantly elevated for osteoporosis (2.81, 95% CI 2.33-3.37), followed by venous thromboembolic diseases (2.36, 95% CI 1.61-3.40), severe infections (1.85, 95% CI 1.57-2.18), thyroid diseases (1.55, 95% CI 1.25-1.91), cerebrovascular accidents (1.40, 95% CI 1.12-1.74), and diabetes mellitus (1.29, 95% CI 1.05-1.56). The RR for ischemic heart disease was elevated, but did not reach statistical significance (1.20, 95% CI 1.00-1.44).Patients with GCA have higher rates of selected comorbidities, including severe infections, compared with a reference population. Several of these comorbidities may be related to treatment with glucocorticosteroids, emphasizing the unmet need to find alternative treatments for GCA.